Home is where the future is: The BrightFocus Foundation consensus panel on dementia care - Samus, Quincy M. (Alzheimers Dement, 2017)
INTRODUCTION: A national consensus panel was convened to develop recommendations on future directions for home-based dementia care (HBDC). METHODS: The panel summarized advantages and challenges of shifting to HBDC as the nexus of care, and developed consensus-based recommendations. RESULTS: The panel developed five core recommendations: (1) HBDC should be considered the nexus of new dementia models, from diagnosis to end of life in dementia; (2) new payment models are needed to support HBDC and reward integration of care; (3) a diverse new workforce that spans the care continuum should be prepared urgently; (4) new technologies to promote communication, monitoring/safety, and symptoms management must be tested, integrated and deployed; and (5) targeted dissemination efforts for HBDC must be employed. DISCUSSION: HBDC represents a promising paradigm shift to improve care for those living with dementia and their family caregivers: these recommendations provide a framework to chart a course forward for HBDC.